A SINGLE-PHASE 220 V AUTOMATIC VOLTAGE REGULATOR BASED ON THE PRINCIPLE OF SPLIT COIL VOLTAGE COMPENSATION TRANSFORMER - Sanajit, Narongrit; Prapurt, Nuttapong; Damrongsak, Ponthakorn (Srinakharinwirot University Journal of Sciences and Technology, 2022)
This paper presents the design and construction of a single-phase automatic voltage regulator, controlling electrical load at constant voltage 220 V and rated power 4 kVA. The design relied on the principle of split coil voltage compensation transformer. A single-phase auto-transformer was connected to the isolate transformer. Feedback control methodology was used to maintain the constant voltage when the voltage input varies from 180-260 V. A purely resistive load (unity power factor) was examined in this research. The result shows that the implementation of the design can regulate voltage output at 220 V with a tolerance of 1% at the rated power range from 1 kVA to 4 kVA and the voltage input can vary as expectation. It demonstrates that over 95% efficiency responds to any voltage variation in 1 second maximum. The design can regulate voltage output in less than 10 second of time, and safety in use was also the concern of the design.